PROBLEM RECEPCJI NA ZACHODZIE NAUKI O OBRAZACH SOBORU NICEJSKIEGO II - Chełstowski, Dariusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The teaching of the Second Vatican Council of 787 on the cult of images has never been fully absorbed by the Western Church. This legacy is particularly relevant today, in the era of image and visual communication, whose use in evangelism seems to be a requirement of our time. It is therefore necessary to conduct a second deeper reflection on the place and role of the sacred image in the Church, and to reach out to the sources, still valid and not fully accepted, the doctrine elaborated by this Council.